Total bile acid to platelet ratio: A noninvasive index for predicting liver fibrosis in primary biliary cholangitis. Issue 22 (29th May 2020) - Jiang, Minjie; Yan, Xin; Song, Xinyue; Yan, Qi; Zhao, Youyou; Wang, Luyuan; Gao, Pujun
Abstract : Abstract: The aim of the study was to develop a new early noninvasive diagnostic model for primary biliary cholangitis (PBC). A total of 118 PBC patients who had undergone a liver biopsy were enrolled in the study, and were randomized into a model group (78 patients) and a validation group (40 patients). The patients' histological stages were based on the classifications of the Scheuer's stage. All common parameters and liver pathological results were analyzed. And total bile acid to platelet ratio, aspartate aminotransferase to platelet ratio index, fibrosis index based on 4 factors and red cell distribution width to platelet ratio were calculated. There were 106 (89.8%) women and 12 men in this study, and the number of patients in Scheuer stage I, II, III, and IV hepatic fibrosis was 52 (44.1%), 36 (30.5%), 26 (22.0%), and 4 (3.4%), respectively. The areas under the receiver operating characteristic curves of the total bile acid to platelet ratio (TPR), the aspartate aminotransferase to platelet ratio index, the fibrosis index based on 4 factors, and the red cell distribution width to platelet ratio for predicting advanced liver fibrosis were 0.771, 0.715, 0.618, and 0.517 respectively. The areas under the receiver operating characteristic curves of the TPR was higher than other non-invasive serological models. As a simple, inexpensive and easily accessible non-invasive liver fibrosis diagnostic model, the TPR may be a new noninvasive marker for predicting histologic severity of PBC.